Development and Application of Pyridinium 1, 4‐Zwitterionic Thiolates: Synthesis of Polysubstituted Thiophenes. Issue 12 (9th March 2020) - Cheng, Bin; Duan, Xiaoguang; Li, Yuntong; Zhang, Xinping; Li, Hui; Wu, Fufang; Li, Yun; Wang, Taimin; Zhai, Hongbin
Abstract : Pyridinium 1, 4‐zwitterionic thiolates as a class of sulfur‐containing synthons were applied to a [3+2] cascade cyclization reaction with activated alkynes, affording a library of polysubstituted thiophenes with excellent regioselectivities, especially those bearing various fluorine‐containing groups. The freshly disclosed pyridinium 1, 4‐zwitterionic thiolates decorated with acyl or trifluoromethyl groups exhibited powerful potential in the synthesis of polysubstituted thiophenes. Of particular note is that pyridinium A4 could introduce sulfur and CF3 groups to target products simultaneously. Abstract : Pyridinium 1, 4‐zwitterionic thiolates as a class of sulfur‐containing synthons were applied to a [3+2] cascade cyclization reaction with activated alkynes, affording a library of polysubstituted thiophenes with excellent regioselectivities, especially those bearing multifarious fluorine‐containing groups.